BIODEGRADASI LIMBAH OLI BEKAS OLEH Lycinibacillus sphaericus TCP C 2.1 - Witono Basuki (Jurnal Teknologi Lingkungan, 2011)
Mikroorganism has capability to degrade used engine oil was isolated from soil sample contaminated with used engine oil. One of the selected strain TCP C 2.1 was identified by 16s rDNA as Lycinibacillus sphaericus. The microorganism can use hydrocarbon in used engine oil as the sole carbon source and energy, also it significantly degraded almost all hydrocarbon compounds in used engine oil. With its ability the microorganism has potency to be used as a single microbe for bioremediation of soil polluted by engine oil.